Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.4093/dmj.2021.0132
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Dose Persistent Organic Pollutants on Mitochondrial Function: Human and in Vitro Evidence

Abstract: Background: Chronic exposure to low-dose persistent organic pollutants (POPs) can induce mitochondrial dysfunction. This study evaluated the association between serum POP concentrations and oxygen consumption rate (OCR) as a marker of mitochondrial function in humans and in vitro cells. Methods: Serum concentrations of organochlorine pesticides (OCPs) and polychlorinated biphenyls (PCBs) were measured in 323 adults. The OCRs of platelets and peripheral blood mononuclear cells (PBMCs) were assessed in 20 mL of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…However, the visual examination of the cultures ( Figure 1 ) did not support a substantial difference in cell number between cultures initially exposed to DMSO and those exposed to PCB126. Another possible explanation for the decrease in ATP levels observed in cells exposed to PCB126 before differentiation could reside in the fact that POPs have been shown to impair mitochondrial oxygen consumption and ATP production, especially in the longer term, in vivo and in vitro [ 54 , 55 , 56 ]. While further investigations are required to explain the observed delayed decrease in ATP levels 14 days following PCB126 exposure, media LDH activity, cellular ADP/ATP ratio and visual examination strongly suggest that the cells’ viability was not compromised.…”
Section: Discussionmentioning
confidence: 99%
“…However, the visual examination of the cultures ( Figure 1 ) did not support a substantial difference in cell number between cultures initially exposed to DMSO and those exposed to PCB126. Another possible explanation for the decrease in ATP levels observed in cells exposed to PCB126 before differentiation could reside in the fact that POPs have been shown to impair mitochondrial oxygen consumption and ATP production, especially in the longer term, in vivo and in vitro [ 54 , 55 , 56 ]. While further investigations are required to explain the observed delayed decrease in ATP levels 14 days following PCB126 exposure, media LDH activity, cellular ADP/ATP ratio and visual examination strongly suggest that the cells’ viability was not compromised.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, chronic exposure to low‐dose POPs has been linked to the risk of many chronic diseases including type 2 diabetes mellitus and cardiovascular diseases in the general population 3 , 4 . Although high doses of individual compounds belonging to POPs are well‐known mitochondrial toxins, a recent human and in vitro study demonstrated that even low‐dose POPs can impair mitochondrial function through the impairment of oxidative phosphorylation 5 . Therefore, chronic exposure to low‐dose POPs might be involved in the development of a wide range of mitochondrial dysfunction‐related diseases.…”
Section: How Can Dynamics Of Lipophilic Pollutants Be Linked To Obesi...mentioning
confidence: 99%
“…While early toxicological studies have primarily focused on acute chemical-induced mitochondrial toxicity at high doses, recent research highlighted the adverse effects of chronic exposure to low doses. Such exposure can lead to gradual mitochondrial dysfunction, especially by disrupting oxidative phosphorylation within the electron transport chain (6).…”
mentioning
confidence: 99%
“…In addition, adipose tissue also secretes cytokines, such as adiponectin and leptin. These have anti-inflammatory effects and may help to counteract the inflammatory response in sepsis (6). Furthermore, obesity presents a "preconditioning" effect against the proinflammatory cascade.…”
mentioning
confidence: 99%